DETERMINATION OF REDUCING POWER AND PHYTOCHEMICAL PROFILE OF THE CHILEAN MISTLETOE "QUINTRAL" (Tristerix corymbosus (L) Kuijt) HOSTED IN “MAQUI” (Aristotelia chilensis), “HUAYÚN” (Rhaphitamnus spinosus) AND “POPLAR” (Populus nigra). - Torres Neyra, Patricio; Saldaña, Cecilia; Ortega Rojas, Ruth; González Ponce, Christopher (Journal of the Chilean Chemical Society, 2019)
On the Chilean mistletoe “Quintral”, there has been limited literature, despite the fact the numerous uses and ubiquity amongst the Mapuche natives in Chile and Argentina. Therefore, our research group has carried out an exhaustive extraction with solvents of increasing polarity to Quintral flowers and leaves hosted in three different host species. With the extracts of different polarities, a phytochemical screening was performed, finding the presence of glycosides, sterols, terpenoids and quinones which are documented to convey different applications in cardiovascular or gastric afflictions. Likewise, the content of total phenols, total flavonoids and the reducing power of all the extracts were determined, displaying significant differences for the three varieties. Leaf and flower of the “Huayún Quintral” in methanol extracts gave the highest values of reducing power, while leaf and flower methanol extracts of “Maqui Quintral” showed the highest values for total phenols. Also observed are the lower polarity extracts from Quintral, contributing to the reducing capability by means of non-phenolic compounds.